Quantitative Differences in Nuclear β-catenin and TCF Pattern Embryonic Cells in C. elegans. - Amanda L Zacharias; Travis Walton; Elicia Preston; John Isaac Murray (PLoS Genetics, 2015)
The Wnt signaling pathway plays a conserved role during animal development in transcriptional regulation of distinct targets in different developmental contexts but it remains unclear whether quantitative differences in the nuclear localization of effector proteins TCF and β-catenin contribute to context-specific regulation. We investigated this question in Caenorhabditis elegans embryos by quantifying nuclear localization of fluorescently tagged SYS-1/β-catenin and POP-1/TCF and expression of Wnt ligands at cellular resolution by time-lapse microscopy and automated lineage tracing. We identified reproducible, quantitative differences that generate a subset of Wnt-signaled cells with a significantly higher nuclear concentration of the TCF/β-catenin activating complex. Specifically, β-catenin and TCF are preferentially enriched in nuclei of daughter cells whose parents also had high nuclear levels of that protein, a pattern that could influence developmental gene expression. Consistent with this, we found that expression of synthetic reporters of POP-1-dependent activation is biased towards cells that had high nuclear SYS-1 in consecutive divisions. We identified new genes whose embryonic expression patterns depend on pop-1. Most of these require POP-1 for either transcriptional activation or repression, and targets requiring POP-1 for activation are more likely to be expressed in the cells with high nuclear SYS-1 in consecutive divisions than those requiring POP-1 for repression. Taken together, these results indicate that SYS-1 and POP-1 levels are influenced by the parent cell's SYS-1/POP-1 levels and this may provide an additional mechanism by which POP-1 regulates distinct targets in different developmental contexts.